2023
DOI: 10.1186/s12909-023-04244-x
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical exposure as a highly interesting educational program for undergraduate medical students: an interventional study

Abstract: Background Training professional medical experts is so much dependent on the efficacy of the medical curriculum. Bearing this in mind, we aimed to evaluate the attitude of the undergraduate medical students toward the Early clinical exposure (ECE) program as a facilitator transition to the clinical phase. Methods This quasi-experimental study was conducted on undergraduate medical students at the Mashhad University of Medical Sciences, Mashhad, Ira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…These findings support the possibility that the Introduction of Early Clinical Exposure in perception offered a creative method of providing clinical experiences. Providing early clinical exposure can enhance students' motivation and understanding of the role they will play in the future as a physician (AkbariRad et al, 2023). Specifically, the students indicated that the ECE session was interesting and motivating for them, and it enhanced their understanding of the theoretical concepts of physiology, and helped them appreciate the relevance of practical applications and thereby understand the purpose of learning the subject.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the possibility that the Introduction of Early Clinical Exposure in perception offered a creative method of providing clinical experiences. Providing early clinical exposure can enhance students' motivation and understanding of the role they will play in the future as a physician (AkbariRad et al, 2023). Specifically, the students indicated that the ECE session was interesting and motivating for them, and it enhanced their understanding of the theoretical concepts of physiology, and helped them appreciate the relevance of practical applications and thereby understand the purpose of learning the subject.…”
Section: Resultsmentioning
confidence: 99%
“…However, AI shall not replace the roles of physicians and professors in today’s academia; rather, it may modify the roles [ 36 ]. Due to these developments, the current knowledge of medical students and practicing physicians on AI is likely to foster such an evolution [ 37 , 38 ]. Furthermore, medical education faces pedagogical issues on how AI should be introduced into medical curricula to be maximally effective but not destructive.…”
Section: Discussionmentioning
confidence: 99%